TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Taller and larger: shifts in Arctic tundra leaf traits after 16 years of experimental warming - J. M. G. HUDSON; G. H. R. HENRY; W. K. CORNWELL (Global Change Biology, 2011)
Understanding plant trait responses to elevated temperatures in the Arctic is critical in light of recent and continuing climate change, especially because these traits act as key mechanisms in climate‐vegetation feedbacks. Since 1992, we have artificially warmed three plant communities at Alexandra Fiord, Nunavut, Canada (79°N). In each of the communities, we used open‐top chambers (OTCs) to passively warm vegetation by 1–2 °C. In the summer of 2008, we investigated the intraspecific trait responses of five key species to 16 years of continuous warming. We examined eight traits that quantify different aspects of plant performance: leaf size, specific leaf area (SLA), leaf dry matter content (LDMC), plant height, leaf carbon concentration, leaf nitrogen concentration, leaf carbon isotope discrimination (LCID), and leaf δ 15 N. Long‐term artificial warming affected five traits, including at least one trait in every species studied. The evergreen shrub Cassiope tetragona responded most frequently (increased leaf size and plant height/decreased SLA, leaf carbon concentration, and LCID), followed by the deciduous shrub Salix arctica (increased leaf size and plant height/decreased SLA) and the evergreen shrub Dryas integrifolia (increased leaf size and plant height/decreased LCID), the forb Oxyria digyna (increased leaf size and plant height), and the sedge Eriophorum angustifolium spp. triste (decreased leaf carbon concentration). Warming did not affect δ 15 N, leaf nitrogen concentration, or LDMC. Overall, growth traits were more sensitive to warming than leaf chemistry traits. Notably, we found that responses to warming were sustained, even after many years of treatment. Our work suggests that tundra plants in the High Arctic will show a multifaceted response to warming, often including taller shoots with larger leaves.